Thiol-Based Redox Switches - Groitl, Bastian (2014)
Regulation of protein function through thiol-based redox switches plays an important role in the response and adaptation to local and global changes in the cellular levels of reactive oxygen species (ROS). Redox regulation is used by first responder proteins, such as ROS-specific transcriptional regulators, chaperones or metabolic enzymes to protect cells against mounting levels of oxidants, repair the damage and restore redox homeostasis. Redox regulation of phosphatases and kinases is used to control the activity of select eukaryotic signaling pathways, making reactive oxygen species important second messengers that regulate growth, development and differentiation. In this review we will compare different types of reversible protein thiol modifications, elaborate on their structural and functional consequences and discuss their role in oxidative stress response and ROS adaptation.